تطبيق الألعاب التعليمية لتحسين مهارة قراءة نصوص اللغة العرابية في المدرسة المتوسطة نهضة العلماء كراسان - Dina Kamilia; M sugianto; Shobirin (Yayasan pendidikan dzurriyatul Quran, 2026)
This study aims to examine the use of educational games in improving students’ Arabic reading skills (maharah al-qirā’ah) at the Nahdlatul Ulama Kraksaan School. The problems addressed in this study are students’ low ability to read and understand Arabic texts, as well as a lack of motivation to learn due to the use of monotonous teaching methods. Therefore, a more engaging and interactive teaching method is needed to encourage students to be more active in the learning process.This study employed a descriptive qualitative method. Data collection techniques included observation, interviews, and documentation. The research subjects consisted of Arabic language teachers and students at MA Nahdlatul Ulama Krasaan. Data were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of educational games is effective in enhancing students’ motivation and engagement in Arabic language learning. Additionally, students find it easier to understand Arabic vocabulary and text content. Educational games also help boost students’ confidence and self-assurance when reading Arabic texts in front of the class, thereby making the learning process more effective and enjoyable.